Reduced synaptic tagging by complement protein C3 is associated with elevated extracellular matrix in the middle-aged cerebellum of mice - Düsedau, Henning Peter; Cangalaya, Carla; Stoyanov, Stoyan; Dityatev, Alexander; Dunay, Ildiko Rita (Frontiers in Aging Neuroscience, 2025)
BackgroundAging of the brain is associated with cognitive decline and recognized as a major risk factor for the development of neurodegenerative diseases. On a cellular level, brain aging is accompanied by a progressive increase of the basal pro-inflammatory tonus, leading to the activation of phagocytic pathways in brain-resident microglia and disruptive effects on synaptic neurotransmission. While the aging process affects all brain compartments at different velocities and one of the particularly affected regions is the cerebellum (CB), the underlying effects remain elusive.MethodsIn the present study, we harnessed a murine model of natural aging in males combined with orthogonal experimental approaches comprising of cytokine gene expression analysis, flow cytometry, immunohistochemistry, and flow synaptometry.ResultsWe report age-dependent morphological and phenotypic changes in microglia that are distinct in the cortex (CTX) and CB. Furthermore, we show an increased expression of cytokines and complement factors upon aging and a decline of C3-tagged VGLUT1+ presynaptic puncta in the CB. Using flow synaptometry to quantify the composition of synapses in more detail, we validated the reduction of C3b-labeled excitatory synaptosomes while the overall frequency of glutamatergic synaptosomes remained unaffected by aging. Notably, proteoglycans brevican and aggrecan, key components of the neural extracellular matrix, were significantly upregulated in the middle-aged CB.DiscussionThe data presented herein suggests the ECM-mediated shielding of synapses from complement-tagging and subsequent engulfment by microglia. Thus, we provide novel insights into mechanisms that may confer resilience in the brain by modulating synapse removal in the context of aging.